PURCHASE DETERMINANTS OF DURABLE GOODS FOR RESIDENTS OF LARGE CITIES IN POLAND (Polityki Europejskie, Finanse i Marketing)
The article presents an analysis of purchase determinants for individual consumers of durable goods in 6 large cities in Poland. The analysis has been based on the outcomes of consumer research carried out in the years 2016 and 2017 at Poznan University of Economics and Business, as well as on other research studies published in Polish publications. The results of the study demonstrate groups of determinants that shape the purchasing decisions of consumers of durable products, as well as their variability in years 2016 and 2017.